Functional Connectivity Disruption in Neonates with Prenatal Marijuana Exposure - Grewen, Karen; Salzwedel, Andrew P.; Gao, Wei (Frontiers in Human Neuroscience, 2015)
Prenatal marijuana exposure (PME) is linked to neurobehavioral and cognitive impairments, however findings in childhood and adolescence are inconsistent. Type-1 cannabinoid receptors (CB1R) modulate fetal neurodevelopment, mediating PME effects on growth of functional circuitry sub-serving behaviors critical for academic and social success. The purpose of this study was to investigate the effects of prenatal marijuana on development of early brain functional circuitry prior to prolonged postnatal environmental influences. We measured resting state functional connectivity during unsedated sleep in infants at 2-6 weeks (+MJ: 20 with PME in combination with nicotine, alcohol, opiates, and/or SSRI; -MJ: 23 exposed to the same other drugs without marijuana, CTR: 20 drug free controls). Connectivity of subcortical seed regions with high fetal CB1R expression was examined. Marijuana-specific differences were observed in insula and three striatal connections: anterior insula – cerebellum, right caudate – cerebellum, right caudate – right fusiform gyrus/inferior occipital, left caudate – cerebellum. +MJ neonates had hypoconnectivity in all clusters compared with -MJ and CTR groups. Altered striatal connectivity to areas involved in visual spatial and motor learning, attention, and in fine-tuning of motor outputs involved in movement and language production may contribute to neurobehavioral deficits reported in this at-risk group. Disrupted anterior insula connectivity may contribute to altered integration of interoceptive signals with salience estimates, motivation, decision-making, and later drug use. Compared with CTRs, both +MJ and -MJ groups demonstrated hyperconnectivity of left amygdala seed with orbital frontal cortex and hypoconnectivity of posterior thalamus seed with hippocampus, suggesting vulnerability to multiple drugs in these circuits.